PENERAPAN HIGIENE SANITASI JASA BOGA PADA KATERING GOLONGAN A2 DAN GOLONGAN A3 DI KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Karina Septea Asie Sawong; Dini Ririn Andrias; Lailatul Muniroh (Media Gizi Indonesia, 2016)
The rapid development of new caterings without followed by supervision from the authorities in term of food safety could lead to food safety cases. This study aimed to analyze the application of hygiene sanitation in catering class A2and A3 in Palangka Raya. This research was conducted with descriptive observational design non-hypothesis. The primary data obtained through interview about characteristics of catering at 10 selected caterings (3 caterings class A2 and 7 caterings class A3) and observation of building, sanitary facilities, equipments, food handlers, foods, principles of hygiene and sanitation, and quality of food microbiology. Sample was selected based on purposive technique. Data were analyzed descriptively. The result showed entire catering still does not meet physical requirements in the application of hygiene sanitation catering (catering group A2 grades 70-74; class A3 grades 74-83). The application of principles hygiene and sanitation each variable in several caterings was met requirements. Assessment of the microbiological quality of vegetables menu in 3 caterings shows number of bacteria E.coli were 0/g. The conclusion of research in general is that principle the application of hygiene sanitation principle and microbiological quality are met by the catering class A2 and A3 in Palangka Raya. However, the physical feasibility still needs to be improved. Application of hygiene and sanitation in caterings are expected to be a reference to obtain hygiene certifi cate acceptance as well as information to Health Department for verify the application of hygiene and sanitation catering in Palangka Raya.Keywords: E.coli, hygiene and sanitation, catering